Mechanisms and biological importance of photon-induced bystander responses: do they have an impact on low-dose radiation responses - Tomita, Masanori (J Radiat Res, 2015)
Elucidating the biological effect of low linear energy transfer (LET), low-dose and/or low-dose-rate ionizing radiation is essential in ensuring radiation safety. Over the past two decades, non-targeted effects, which are not only a direct consequence of radiation-induced initial lesions produced in cellular DNA but also of intra- and inter-cellular communications involving both targeted and non-targeted cells, have been reported and are currently defining a new paradigm in radiation biology. These effects include radiation-induced adaptive response, low-dose hypersensitivity, genomic instability, and radiation-induced bystander response (RIBR). RIBR is generally defined as a cellular response that is induced in non-irradiated cells that receive bystander signals from directly irradiated cells. RIBR could thus play an important biological role in low-dose irradiation conditions. However, this suggestion was mainly based on findings obtained using high-LET charged-particle radiations. The human population (especially the Japanese, who are exposed to lower doses of radon than the world average) is more frequently exposed to low-LET photons (X-rays or γ-rays) than to high-LET charged-particle radiation on a daily basis. There are currently a growing number of reports describing a distinguishing feature between photon-induced bystander response and high-LET RIBR. In particular, photon-induced bystander response is strongly influenced by irradiation dose, the irradiated region of the targeted cells, and p53 status. The present review focuses on the photon-induced bystander response, and discusses its impact on the low-dose radiation effect.